Iqbal: The man and his mission in life - Abdul Razak, Mohd Abbas (2017)
After the time of the Prophet of Islam, Muslims and their civilization started to flourish giving rise to many vast empires stretching from Granada to Indonesia. Muslim scholars became great authorities in the many fields of knowledge. During the Golden Age of Islam (750-1258), Muslims were the pioneers, inventors, innovators in the human and natural sciences. Practically, they were interested in all areas of investigation that later became the foundation and spark for further development of science and technology during the modern times of humanity. All this great achievements went missing when the Islamic empires started to fall and disintegrate. This situation started to deteriorate further in the Muslim world with the coming of the era of colonization and neo-colonization. During the time of mental crisis, intellectual lethargy, backwardness and lose of direction that happened within the Muslim Ummah there came great minds calling the masses to the ideal situation once they enjoyed on the world stage. One among the many reformers that came to call Muslims to return to their dynamic lifestyle, vision and mission in life was Allama Muhammad Iqbal (1877-1937). Iqbal, who has been taught by the best minds of the East and West later developed and formulated solutions of his own to remedy the many shortcomings of the Muslim Ummah. As a poet-philosopher of international repute, Iqbal called for the co-existence of civilizations and the creation of a better world. This small-scale qualitative research is a humble attempt to introduce and highlight some of Iqbal’s life history, formulation of his philosophy, mission and vision of his life and challenges faced by him.